The Impact of VUCA Prime on The Performance of The Automotive Industry in Indonesia - Sanusi, M. Dudi Abdullah; Purwoko, Bambang; Widyastuti, Sri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to identify and analyze the potential challenges of VUCA to the development of the automotive industry in Indonesia and their impact on company performance. The research uses VUCA Prime as a tool to antidote VUCA. The method used in this research is descriptive and verification research methods. The research sample was 248 respondents based on manager-level positions and above using a purposive sampling method. The results showed that VUCA Prime had a positive and significant effect on agile leadership and company performance. VUCA Prime had a positive and significant effect on Strategic business. VUCA Prime had a positive and significant effect on Organizational change. VUCA Prime has a positive and significant effect on the performance of automotive industry companies in Indonesia. Agile leadership is intervening in the influence between VUCA Prime and company performance. Organizational change is intervening between VUCA Prime and company performance. Strategic business is intervening between VUCA Prime and company performance in automotive industry companies in Indonesia. Variable intervening results in leadership agility and organizational change, which has a big role in company performance. Research using quality methods through SWOT diagrams leads to a diversification strategy toward 2030